Individual and combined contamination of oxytetracycline and cadmium inhibited nitrification by inhibiting ammonia oxidizers - Cao, Xiaoxu; Zhao, Wei; Zhang, He; Lin, Jitong; Hu, Jingying; Lou, Yanhong; Wang, Hui; Yang, Quangang; Pan, Hong; Zhuge, Yuping (Frontiers in Microbiology, 2022)
The large-scale development of animal husbandry and industrialization lead to more and more serious co-contamination from heavy metals and antibiotics in soils. Ecotoxic effects of residues from antibiotics and heavy metals are of increasing concern. In this study, oxytetracycline (OTC) and cadmium (Cd) were selected as target pollutants to evaluate the individual and combined effects on nitrification process using four different soil types sampled from North to South China through a 56-day incubation experiment. The results demonstrated that the contaminations of OTC and Cd, especially combined pollution had significant inhibitory effects on net nitrification rates (NNRs) as well as on AOA and AOB abundance. The toxic effects of contaminants were greatly enhanced with increasing OTC concentration. AOB was more sensitive than AOA to exogenous contaminants. And the interaction effects of OTC and Cd on ammonia oxidizers were mainly antagonistic. Furthermore, Cd contaminant (with or without OTC) had indirect effects on nitrification activity via inhibiting mineral N and AOA/AOB, while OTC alone indirectly inhibited nitrification activity by inhibiting ammonia oxidizers. The results could provide theoretical foundation for exploring the eco-environmental risks of antibiotics and heavy metals, as well as their toxic effects on nitrification processes.